Dynamics and challenges of the institutional crisis in Ecuador - Salazar-Ponce, Erick Geovanny; Díaz-Romero, Yenniffer; Bueno-Fernández, Mario Mitsuo; Salazar Echeagaray, Teresa Irina (Revista de Ciencias Sociales, 2025)
In recent decades, Ecuador has faced periods of significant institutional crisis characterized by political instability, conflicts among branches of government, and a decline in public trust in institutions. This situation has sparked extensive academic interest in understanding the underlying causes, dynamics, and effects of such crises on democracy and governance in the country. The objective of this study is to analyze the dynamics and challenges of the institutional crisis in Ecuador through a qualitative methodology based on the documentary analysis of bibliographic sources. The findings reveal that the institutional crisis in Ecuador is examined from a broad perspective that integrates theories on institutional crises, democracy, governance, and political crisis analysis. Furthermore, the study highlights the importance of understanding institutional destabilization and dysfunction by analyzing the interaction between these elements, emphasizing the impact of institutional uncertainty and the complex distribution of power on governance effectiveness and public policy implementation. The study concludes with the critical need to promote transparency, accountability, and citizen participation as fundamental strategies to overcome the institutional crisis in Ecuador.